Megadont mandibular permanent incisor tooth with Talon Cusp : a case report - Ardini, Yunita Dewi; Harun, Nor Asilah (2012)
Megadont is an uncommon developmental anomaly in which one or more teeth in a dentition are larger than normal. A megadont crown is resulted from fusion of two tooth germs (fusion) or a separation of a single tooth to produce two separate teeth (gemination). A variety of terms have been used for this situation. The terms 'double teeth' has been applied to cover both situation. Gemination and fusion have been reported to occur in the primary teeth in 0.5% to 2.5% of Caucasian children. It is more common in Asian children, where 5% of them have this condition. The permanent dentition is less commonly affected (prevalence 0.1%-0.2%). Males and females are affected equally. Gemination and fusion can oocur in the mandibular teeth as well. A talon cusp is an accessory cusp located in the area of the cingulum of a maxillary or mandibular permanent incisor. In this case, megadont of permanent teeth with talon cusp was found during clinical examination in the mandible and associated with hypodontia of an adjacent tooth. Megadont tooth may lead to certain problems such as caries formation, aesthetics and occlusion.